The Influence of Internet Advertising, Sales Promotion and Peer Group on Interest Buying of Fashion Product in Online Fashion Store - Angga Andaru, Yanu; Pradekso, M.Sc, Drs. Tandiyo (Interaksi Online, 2016)
Businesses operating online fashion stores take advantage of the promotional mix of online advertising and sales promotion in marketing their products. Advertisement and sales promotion perform intensively, causing the liability of their consumers exposed to its online messages advertising and sales promotion. The exposure may have an impact on the emergence of consumer interest to purchase fashion products at online fashion store. There also other factor that can give impacts is the exposure of peer group persuasion. The purpose of this research is to determine the influence of internet advertising, sales promotion and peer group against interest of buying fashion products in online fashion store. The research theory of this thesis used the Advertising Exposure Theory, Behavioral Learning Theory and Darley, Blankson and Luethge's Model. This research using purposive type of non-probability sampling technique with total 50 samples whose minimum age requirement is 18-25 years old living in Semarang City; who can access the internet, seen the advertisement online fashion store, and never purchased fashion products at online fashion store before. The results of simple linear regression analysis showed that internet advertising has a positive and significant influence on the interest of buying fashion products in the online fashion store; it proofed from the significant value in the amount of 0.000 which is smaller than 0.01 and the regression coefficients showed a positive value in the amount of 0.304. Sales promotion also has a positive and significant influence on the interest of buying fashion products in the online fashion store; it proofed from the significant value in the amount of 0.000 which is smaller than 0.01 and the regression coefficients showed a positive value in the amount of 0.633. The last is peer group exposure that also has a positive and significant influence on the interest buyer of fashion products in the online fashion store; it proofed from the significant value in the amount of 0.000 which is smaller than 0.01 and the regression coefficients showed a positive value in the amount of 0.818. Contributions effect of internet advertising and peer group is considerable enough to the interest of buying fashion products in online fashion store, while the contributions of sales promotion had not considerable enough to the interest of buying. With the results of that, the advice that can be given is online fashion businessman preferably have to make the design of sales promotion more varied, interesting and easy to understand; so the information can be absorbed by the consumers; and the online fashion store businesses have also reduce the amount of administration of sales promotion by the form of discount and voucher, this had to be done as an effort to reduce costs in product marketing because less effective and to minimize loss value that will be suffer by online fashion businessman.